2002
DOI: 10.1116/1.1465447
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic and structural properties of Fe, Ni, and Mn-implanted SiC

Abstract: Direct implantation of Fe, Ni or Mn at doses of 3–5×1016 cm−2 into p-type 6H-SiC substrates was carried out at a sample temperature of ∼350 °C. Subsequent annealing was performed at 700–1000 °C for 5 mins. Residual damage in the form of end-of-range defects and dislocation loops in the region from the surface to a depth of ∼0.20 μm were examined by transmission electron microscopy. To the sensitivity of both x-ray diffraction and selected area diffraction pattern analysis, no secondary phases could be detected… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
22
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 73 publications
(25 citation statements)
references
References 26 publications
2
22
1
Order By: Relevance
“…Nevertheless, the existence of free holes may have led to an additional, hole-mediated exchange interaction playing the role in stabilizing ferromagnetism at larger distances between the impurities. At least some of the experimental studies of Fe-doped SiC reported ferromagnetic DMS behaviour in Fe-implanted 6H-SiC (Theodoropoulou et al, 2002;Stromberg et al, 2006). Our calculations reveal nonmagnetic ground state and antiferromagnetic ordering in the magnetic state of (Si, Fe) C. Such discrepancy may be explained by several factors.…”
Section: Concluding Remarks and Outlookcontrasting
confidence: 45%
See 2 more Smart Citations
“…Nevertheless, the existence of free holes may have led to an additional, hole-mediated exchange interaction playing the role in stabilizing ferromagnetism at larger distances between the impurities. At least some of the experimental studies of Fe-doped SiC reported ferromagnetic DMS behaviour in Fe-implanted 6H-SiC (Theodoropoulou et al, 2002;Stromberg et al, 2006). Our calculations reveal nonmagnetic ground state and antiferromagnetic ordering in the magnetic state of (Si, Fe) C. Such discrepancy may be explained by several factors.…”
Section: Concluding Remarks and Outlookcontrasting
confidence: 45%
“…This, for example, may lead to the magnetic state (ferromagnetic or antiferromagnetic) becoming energetically favourable, compared to the nonmagnetic state, in the case of Fe in SiC, for which the ground state solution is nonmagnetic. This possibility of changing the state preference may explain the magnetic response reported in several experimental studies of Fe-doped SiC (Theodoropoulou et al, 2002;Stromberg et al, 2006). Furthermore, the fact that the magnetic and nonmagnetic solutions are separated by an energy gap comparable to room temperature thermal energy, allows us to suggest that a new equilibrium mixed state with a certain distribution of TM atoms between the magnetic and nonmagnetic states, and an average over this distribution magnetic moment, may be created at a nonzero temperature.…”
Section: Magnetic-nonmagnetic State Relationship and Mixingmentioning
confidence: 75%
See 1 more Smart Citation
“…regions of doping levels near 3-5 atomic % [179]. They found no evidence of second-phase formation in their samples with magnetization measurements yielding FM transitions at 50 K for Ni doping, 250 K for Mn, and 270 K for Fe doping.…”
Section: Sic-based Magnetic Semiconductorsmentioning
confidence: 87%
“…The possibility to use spin polarization to create new functionalities for electronics and photonics makes this field interesting for the semiconductor industry. Triggered by its unique properties for high power devices, during the last decade a considerable amount of work was also performed on possible applications of silicon carbide in spintronics [3,4]. To achieve this goal there are three major issues to solve: the material must be a ferromagnetic semiconductor, the value of the Curie temperature must be around room temperature (or above) and the matrix must remain a dilute solution instead of forming metal clusters or second phases.…”
Section: Introductionmentioning
confidence: 99%